Solvent crystallization-induced porous polyurethane/graphene composite foams for pressure sensing. (1st August 2020) - Feng, Chunfang; Yi, Zhifeng; Jin, Xing; Seraji, Seyed Mohsen; Dong, Yajie; Kong, Lingxue; Salim, Nisa
Abstract: Fabrication of facile and scalable flexible graphene-based composite materials offer many advantages and have promising applications as pressure sensors. However, fabricating graphene-based materials with high and wide-range pressure sensitivity in a facile and large-scale way remains a big challenge. Current study details a simple solvent crystallization method to fabricate porous polyurethane and graphene (PU/G) foams with outstanding mechanical stability that can be made into any shape and size. The microstructure and performance of the PU/G foams confirm an ultra-high sensitivity of 7.62 kPa −1 and a super wide pressure range up to 500 kPa with high stability. More importantly, as prepared composite foams can be naturally attached to detect body motions such as finger bending, walking and jumping, which renders its applications in various areas for pressure sensing. As developed PU/G pressure sensor has demonstrated sensing capabilities in monitoring body motions from subtle actions to vigorous activities. Graphical abstract: Image 1